'Stargazers at the world's end': telescopes, observatories and 'views' of empire in the nineteenth-century British Empire. Issue 3 (3rd August 2011) - MCALEER, JOHN
Abstract: This article argues that the study of astronomical observing instruments, their transportation around the globe and the personal and professional networks created by such exchanges are useful conceptual tools in exploring the role of science in the nineteenth-century British Empire. The shipping of scientific instruments highlights the physical and material connections that bound the empire together. Large, heavy and fragile objects, such as transit circles, were difficult to transport and repair. As such, the logistical difficulties associated with their movement illustrate the limitations of colonial scientific enterprises and their reliance on European centres. The discussion also examines the impact of the circulation of such objects on observatories and astronomers working in southern Africa, India and St Helena by tracing the connections between these places and British scientific institutions, London-based instrument-makers, and staff at the Royal Observatory, Greenwich. It explores the ways in which astronomy generally, and the use of observing instruments in particular, relate to broader themes about the applications of science, the development of colonial identities, and the consolidation of empire in the first half of the nineteenth century. In considering these issues, the article illustrates the symbiotic relationship between science and empire in the period, demonstrating the overlap between political and strategic considerations and purely scientific endeavours. Almost paradoxically, as they trained their sights and their telescopes on the heavens, astronomers and observers helped to draw diverse regions of the earth beneath closer together. By tracing the movement of instruments and the arcs of patronage, cooperation and power that these trajectories inscribe, the role of science and scientific objects in forging global links and influencing the dynamics of the nineteenth-century British Empire is brought into greater focus.